"I talked to my doctor:" Constructing the neoliberal patient-consumer in direct-to-consumer pharmaceutical advertising. (April 2019) - Defibaugh, Staci
Highlights: DCTAs position viewers as ultimately responsible for their health. Imperatives direct viewers to complete actions normally associated with providers. Syntactic structures used in DCTAs serve to minimize providers' roles in healthcare. The patient-narrator serves to model the ideal patient-consumer behavior. Abstract: Television direct-to-consumer advertising for prescription drugs (DTCA) has become a pervasive presence for healthcare consumers in the US over the past twenty years. While some scholars have focused on the potential effects these ads have on healthcare, this study takes a critical approach to the ways in which the language used in these ads position viewers as 'patient-consumers' within the neoliberal paradigm. Using a framework of critical discourse analysis, I analyze 15 DTCAs and highlight the specific ways in which medical neoliberalism is reproduced in these ads, focusing specifically on how viewers are positioned as the primary agent for their health through a series of imperatives. In addition to interpellating the viewer as the 'patient consumer, ' many of the ads also employ a strategy of presenting characters who represent the ideal 'patient consumer, ' whom viewers are encouraged to emulate. While this may seem to be a positive move in terms of activating patients, it can set up a false expectation of personal autonomy for patients, often minimizing the role that medical providers play in determining the best course of treatment for a particular patient.